Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1089/pop.2021.0283
|View full text |Cite
|
Sign up to set email alerts
|

Reach of a Fully Digital Diabetes Prevention Program in Health Professional Shortage Areas

Abstract: The National Diabetes Prevention Program (NDPP) offers lifestyle change education to adults at risk for diabetes across the United States, but its reach is curbed due, in part, to limitations of traditional in-person programs. Diabetes Prevention Programs (DPPs) that are fully digital may increase reach by overcoming these barriers. The aim of this research was to examine the reach of Lark's DPP, a fully digital artificial-intelligence-powered DPP. This study assessed geographic features and demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The Facebook ® group utilized in the current trial, which involved minimal intervention by the lifestyle coach, is thus similar to the online delivery format that is currently eligible to receive approval for delivery of the NDPP through the CDC-NDPP recognition program [ 22 ]. Although the weight loss across 6 months in the Facebook ® group was small (−1.68 kg, −1.6%, 7% ≥5%) minimal lifestyle coach burden and the low cost of intervention delivery suggest that additional trials to evaluate strategies to improve the effectiveness Facebook ® for the delivery of the NDPP to rural residents may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The Facebook ® group utilized in the current trial, which involved minimal intervention by the lifestyle coach, is thus similar to the online delivery format that is currently eligible to receive approval for delivery of the NDPP through the CDC-NDPP recognition program [ 22 ]. Although the weight loss across 6 months in the Facebook ® group was small (−1.68 kg, −1.6%, 7% ≥5%) minimal lifestyle coach burden and the low cost of intervention delivery suggest that additional trials to evaluate strategies to improve the effectiveness Facebook ® for the delivery of the NDPP to rural residents may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The BRIDGE initiative will preserve the structural curriculum but will expand the number and quality of resources for older adults. This work will help inform the development of community and clinical programs, as currently less than 15% of rural counties and 48% of urban counties in the nation have a DPP site [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals with very high BMI tend to delay or avoid healthcare visits and tend to have lower participation in lifestyle change programs, in part due to emotional barriers, such as perceived weight stigma from providers [33]. We have previously shown that AI-driven lifestyle change programs tend to enroll higher rates of users with high BMI compared to in-person programs [34], suggesting that AI-driven coaching may be more appealing to individuals with higher BMIs, as it reduces the possibility of experiencing provider stigma. This is crucial, given that a key objective for the Heart Health program is reaching and engaging potential users with high BMI.…”
Section: Plos Digital Healthmentioning
confidence: 99%